2019
DOI: 10.1002/eat.23163
|View full text |Cite
|
Sign up to set email alerts
|

Editorial to the virtual issue highlighting neuroscience based research in eating disorders to mark the 49th Society for Neuroscience Annual Meeting

Abstract: Objective This virtual issue of the International Journal of Eating Disorders highlights recently published research that is based on neuroscience concepts, to mark the 49th Society for Neuroscience Annual Meeting in Chicago, IL, in November 2019. Methods and Results The collection of articles includes research published between 2018 and 2019 that fall within the broader field of clinical neuroscience. Those articles span a broad range of themes, including food intake regulation and reward circuitry, taste per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…A first evidence is that very few studies explored the neurobiological correlates of implicit attitudes related to eating behaviour. Neuroscientific investigation of eating behaviour has increased in the past decades supporting a brain-based approach to eating disorders and outlining different neurobiological models, which represent the rationale for combining psychotherapy and biological treatments ( Val-Laillet et al , 2015 ; Frank, 2019 ). Neuroimaging studies reported the involvement of emotional and reward neuronal circuits in monitoring eating behaviour, and neuromodulation treatments have been tested targeting these circuits ( Val-Laillet et al , 2015 ; Hall et al , 2018b ).…”
Section: Discussionmentioning
confidence: 99%
“…A first evidence is that very few studies explored the neurobiological correlates of implicit attitudes related to eating behaviour. Neuroscientific investigation of eating behaviour has increased in the past decades supporting a brain-based approach to eating disorders and outlining different neurobiological models, which represent the rationale for combining psychotherapy and biological treatments ( Val-Laillet et al , 2015 ; Frank, 2019 ). Neuroimaging studies reported the involvement of emotional and reward neuronal circuits in monitoring eating behaviour, and neuromodulation treatments have been tested targeting these circuits ( Val-Laillet et al , 2015 ; Hall et al , 2018b ).…”
Section: Discussionmentioning
confidence: 99%